Perancangan Sistem Informasi Pemesanan Peralatan Camping Berbasis Web pada Atap Bumi Adventure - Raffi Salman Hakim; Ria Ester; Muhammad Arifin Ilham; Resin Mispar Ludji (PT. Hasba Edukasi Mandiri, 2025)
The need for digital transformation has become crucial for micro, small, and medium enterprises (MSMEs), especially within the equipment leasing sector. Atap Bumi Adventure, a business specializing in camping gear rentals, previously relied on manual methods for managing orders, which led to inefficiencies such as inconsistent records and communication delays. This research is intended to create and implement an online ordering system by applying the waterfall model. The system was created using PHP and MySQL, with an emphasis on a responsive and user-friendly interface. Key features include an equipment catalog, shopping cart, order form, and separate login access for admins and customers. The implementation of this system has significantly improved transaction speed, data accuracy, and customer convenience. Black-box testing confirmed that all core functions performed as expected, indicating the system's readiness for real-world application.